Seroma: an interesting case report - Reddy, Hymavathi K.; J, Ujwala; M, Swetha; Ramya, Shilpa B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
A seroma is defined as a sterile accumulation of serum in a circumscribed location in the tissue. Seromas can occur after surgeries, especially those that are extensive or involve significant tissue disruption viz. hernia repairs, plastic surgeries such as breast augmentation or reconstruction, abdominoplasties (tummy tucks)and removal of large intra-abdominal space occupying lesions like huge fibroids/ovarian masses. The literature citing the exact incidence of seromas following removal of large intra-abdominal masses is scant. Seromas at times become severely symptomatic. The best way to prevent a seroma is not to give it any place to form. It's easier said than done. Here is an interesting case report of postoperative seroma following removal of a large broad ligament fibroid.